Nuclear functions of mammalian MicroRNAs in gene regulation, immunity and cancer - Liu, Hongyu (Mol Cancer, 2018)
MicroRNAs (miRNAs) are endogenous non-coding RNAs that contain approximately 22 nucleotides. They serve as key regulators in various biological processes and their dysregulation is implicated in many diseases including cancer and autoimmune disorders. It has been well established that the maturation of miRNAs occurs in the cytoplasm and miRNAs exert post-transcriptional gene silencing (PTGS) via RNA-induced silencing complex (RISC) pathway in the cytoplasm. However, numerous studies reaffirm the existence of mature miRNA in the nucleus, and nucleus-cytoplasm transport mechanism has also been illustrated. Moreover, active regulatory functions of nuclear miRNAs were found including PTGS, transcriptional gene silencing (TGS), and transcriptional gene activation (TGA), in which miRNAs bind nascent RNA transcripts, gene promoter regions or enhancer regions and exert further effects via epigenetic pathways. Based on existing interaction rules, some miRNA binding sites prediction software tools are developed, which are evaluated in this article. In addition, we attempt to explore and review the nuclear functions of miRNA in immunity, tumorigenesis and invasiveness of tumor. As a non-canonical aspect of miRNA action, nuclear miRNAs supplement miRNA regulatory networks and could be applied in miRNA based therapies.